Evolving Concepts of Dyslexia and Their Implications for Research and Remediation - Protopapas, Athanassios (Frontiers in Psychology, 2019)
Aspects of dyslexia definitions are framed as a contrast between the past and the future, focusing on implications for research and remedial education, highlighting assumptions that bias or limit research or clinical practice. A crucial development is evident in understanding dyslexia, moving from its conceptualization as a discrete identifiable condition towards the realization of continuity with the general population with no clear boundaries and no qualitative differences. This conceptual evolution amounts to a transition from considering dyslexia to be some entity that causes poor reading toward considering the term dyslexia to simply label poor reading performance. This renders obsolete any searches for abnormalities and directs efforts toward understanding reading skill as a multifaceted domain following a complex multifactorial developmental course.